Risk of cardiovascular disease after hospital-diagnosed overweight or obesity - Sigrid Bjerge Gribsholt; Morten Schmidt; Eskild Bendix Kristiansen; Bjørn Richelsen; Henrik Toft Sørensen (Endocrine Connections, 2024)
Objective: The aim was to examine the association between hospital-diagnosed overweight/obesity and incident CVD according to the time period of the overweight/obesity diagnosis. Design: This is a cohort study. Methods: From Danish national health registries, we identified all residents with a first-time hospital-based overweight/obesity diagnosis code, 1977–2018 (n = 195,221), and an age and sex-matched general population comparison cohort (n = 1,952,210). We computed adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) using Cox regression. We adjusted for comorbidities and educational level and applied 10 years of follow-up. Results: The overall incidence rate was 10.1 (95% CI 10.0–10.1) per 1000 person-years for the comparison cohort and 25.1 (95% CI 24.8–25.4) per 1000 person-years for the overweight/obesity cohort, corresponding to an aHR of 2.5 (95% CI 2.4–2.5). The aHR was elevated for all subtypes of CVD: heart failure: 3.9 (95% CI 3.7–4.1), bradyarrhythmia: 2.9 (95% CI 2.7–3.1), angina pectoris: 2.7 (95% CI 2.7–2.8), atrial fibrillation or flutter: 2.6 (95% CI 2.5–2.6), acute myocardial infarction: 2.4 (95% CI 2.3–2.4), revascularization procedure: 2.4 (95% CI 2.2–2.5), valvular heart disease: 1.7 (95% CI 1.6–1.8), ischemic stroke: 1.6 (95% CI 1.4–1.7), transient ischemic attack: 1.6 (95% CI 1.5–1.7), and cardiovascular death: 1.6 (95% CI 1.5–1.6). The 1–10-year aHR of any CVD associated with an overweight/obesity diagnosis decreased from 2.8 (95% CI 2.7–2.9) in 1977–1987 to 1.8 (95% CI 1.8–1.9) in 2008–2018. Conclusion: Patients with hospital-diagnosed overweight/obesity had high rates of ischemic heart disease, heart failure, structural heart disease, arrhythmia, stroke, and death, although the strength of the association decreased in recent years.